2015
DOI: 10.1111/jnc.13424
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways regulating neuron–glia interaction and their implications in Alzheimer's disease

Abstract: Astrocytes are the most abundant cells in the central nervous system. They play critical roles in neuronal homeostasis through their physical properties and neuron-glia signaling pathways. Astrocytes become reactive in response to neuronal injury and this process, referred to as reactive astrogliosis, is a common feature accompanying neurodegenerative conditions, particularly Alzheimer’s disease. Reactive astrogliosis represents a continuum of pathobiological processes and is associated with morphological, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 296 publications
(230 reference statements)
0
51
0
Order By: Relevance
“…Besides complement-mediated synapse removal, other pathways have been described to be involved in glia-neuron interaction that might also result in synapse elimination (reviewed in [ 118 ]). Astrocytes have been described to be implicated in activity-dependent synapse elimination via multiple EGF-like domains 10 (MEGF10) and Mer tyrosine kinase (MERTK) pathways [ 119 ].…”
Section: Other Pathways Involved In Synapse Removalmentioning
confidence: 99%
“…Besides complement-mediated synapse removal, other pathways have been described to be involved in glia-neuron interaction that might also result in synapse elimination (reviewed in [ 118 ]). Astrocytes have been described to be implicated in activity-dependent synapse elimination via multiple EGF-like domains 10 (MEGF10) and Mer tyrosine kinase (MERTK) pathways [ 119 ].…”
Section: Other Pathways Involved In Synapse Removalmentioning
confidence: 99%
“…Prolonged activation of glial cells, microglia and astrocytes in particular, and the release of proinflammatory cytokines, chemokines, and reactive oxygen and nitrogen species, create a neurotoxic environment which could exacerbate the progression of AD (9)(10)(11). Recent genome wide association studies have identified multiple immune related gene variants as risk factors for late-onset AD, supporting a major contributing role of innate immunity and neuroinflammation in AD (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular Ca 2+ concentration ([Ca 2+ ] i ) changes are an important signal for a wide spectrum of cell activities from short-term neurotransmitter release to long-term control of gene expression ( Berridge, 2014 , Lian and Zheng, 2016 , Mintz et al., 1995 , Simms and Zamponi, 2014 , Soderling and Derkach, 2000 , Yagami et al., 2012 ). The voltage-gated Ca 2+ channels (Ca V s) at the plasma membrane are encoded by various isoforms in different cells and are the main pathway for Ca 2+ influx.…”
Section: Introductionmentioning
confidence: 99%